2016
DOI: 10.17511/ijmrr.2016.i08.09
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of midazolam versus clonazepam as premedication scheduled for elective abdominal hysterectomies

Abstract: Background and aim: Anxiety is one of the most common problem which affect the patient during surgical procedures. Thus, anxiolytics have a primary role as premedication preoperatively. With this background, we designed this study to compare anxiolytic effects of oral midazolam and oral clonazepam. Methods: Study was carried out in 80 patients scheduled for elective Abdominal hysterectomy and were divided into group of 40 each. Group M 40 patients were given Tab Midazolam 10 mg, 45 min before surgery. Group C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…But clonazepam found to be better anxiolytic than midazolam. 12 Kumar et al found that buccal clonazepam demonstrated equivalence to I/V midazolam in controlling acute breakthrough seizure. When extrapolated to domiciliary setting it is likely to be safe option with capability of decreasing status episodes, hospitalization and thus reducing economic burden and psychological stress to the family.…”
Section: Resultsmentioning
confidence: 99%
“…But clonazepam found to be better anxiolytic than midazolam. 12 Kumar et al found that buccal clonazepam demonstrated equivalence to I/V midazolam in controlling acute breakthrough seizure. When extrapolated to domiciliary setting it is likely to be safe option with capability of decreasing status episodes, hospitalization and thus reducing economic burden and psychological stress to the family.…”
Section: Resultsmentioning
confidence: 99%